The influence of Silane Coupling Agent and porogen ratio on 3D scaffold PCL/HA - Faqih, Mu'adz Abdullah; Purniawan, Agung; Rasyida, Amaliya; Susanti, Diah (Universitas Mercu Buana, 2025)
The design of scaffold based on polycaprolactone (PCL) and hydroxyapatite (HA) has attracted attention as a solution for bone tissue regeneration. However, the main challenge in its development is the difficulty in achieving an optimal balance between porosity and mechanical strength. Suboptimal porosity limits the scaffold ability to support cell proliferation, and weak mechanical properties result in the scaffold being less than optimal as a load-bearing implant material during the bone cell regeneration process. This study aims to address these issues by evaluating the effects of the silane coupling agent 3-aminopropyltriethoxysilane (APTES) and the porogen ratio (NaCl) on the mechanical properties, morphology, and biodegradation of PCL-HA-based 3D scaffold. The scaffold were synthesized using the solvent casting/particulate leaching (SCPL) method with varying APTES concentrations (1%, 3%, and 5%) and porogen ratios. (4:1, 6:1, and 8:1). The results of characterization show that the addition of 1% APTES increases compressive strength by 283% and tensile strength by 138% compared to scaffold without APTES. A higher porogen ratio (8:1) results in the highest porosity of 78.16%, but reduces mechanical strength by 84%. The optimal combination was found in scaffold with 1% APTES and a porogen ratio of 4:1, which have optimal mechanical strength, porosity of 69.65%, and a biodegradation time of up to 380 days. This research offers a comprehensive solution to enhance the properties of PCL-HA based 3D scaffold, making a significant contribution to the development of materials for bone tissue engineering applications.